PROPOSITION OF A PEIRCEAN SEMIOTIC REALISM TO ONE OF THE VERSIONS OF QUANTUM PHYSICS - Machado, Lino (Laboratório Editorial FCL-UNESP, 2013)
Application of the triadic Semiotics by C. S. Peirce to Quantum Mechanics, as established by the so called Copenhagen School in the 1920’s and reinterpreted by Werner Heisenberg in the 1950’s, with the aid of the Aristotelian notion of  dýnamis-potentia.